2018
DOI: 10.1039/c7fd00213k
|View full text |Cite
|
Sign up to set email alerts
|

Modelling free and oxide-supported nanoalloy catalysts: comparison of bulk-immiscible Pd–Ir and Au–Rh systems and influence of a TiO2 support

Abstract: The relative stabilities of different chemical arrangements of Pd-Ir and Au-Rh nanoalloys (and their pure metal equivalents) are studied, for a range of compositions, for fcc truncated octahedral 38- and 79-atom nanoparticles (NPs). For the 38-atom NPs, comparisons are made of pure and alloy NPs supported on a TiO2(110) slab. The relative energies of different chemical arrangements are found to be similar for Pd-Ir and Au-Rh nanoalloys, and depend on the cohesive and surface energies of the component metals. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This Au/Rh/TiO2 stacking is driven by the stronger affinity of Rh with TiO 2 as compared to Au. By stabilizing the entire structure, such a segregation of Rh at the interface provides a high resistance against sintering to the NPs, as also shown for Pd-Ir/TiO 2 [163], Au-Ir/TiO2 [195], and Cu-Ni/TiO2 [196]. Noticeably, both Cu-Ni/TiO 2 [196] and Au-Rh/TiO2 [104] exhibit synergistic effects for the hydrodeoxygenation of biomass derivatives.…”
Section: Support-directed Segregation In Nanoalloysmentioning
confidence: 71%
See 1 more Smart Citation
“…This Au/Rh/TiO2 stacking is driven by the stronger affinity of Rh with TiO 2 as compared to Au. By stabilizing the entire structure, such a segregation of Rh at the interface provides a high resistance against sintering to the NPs, as also shown for Pd-Ir/TiO 2 [163], Au-Ir/TiO2 [195], and Cu-Ni/TiO2 [196]. Noticeably, both Cu-Ni/TiO 2 [196] and Au-Rh/TiO2 [104] exhibit synergistic effects for the hydrodeoxygenation of biomass derivatives.…”
Section: Support-directed Segregation In Nanoalloysmentioning
confidence: 71%
“…Beyond downsizing, nanoalloying is an additional way of boosting the hydrogen absorption capacity, as shown for Pd-Pt and Ag-Rh systems [160]. In contrast, we have found that nanoalloying Pd with Ir strongly decreases the hydrogen absorption capacity of Pd and suppresses β hydriding [161,162] through the formation of a core-shell Ir@Pd structure (Figure 7, left-hand side) [163,164]. The decreased hydrogen capacity is correlated to a strongly increased preferential CO oxidation activity in the presence of H 2 (PROX process) with respect to pure Pd and Ir counterparts [161,165].…”
Section: Hydrogen Absorption and Hydridingmentioning
confidence: 74%
“…Initial evaluation of CP1À Au revealed only minimal activity in AB decomposition in methanol, and we then proceeded to evaluate bimetallic system through incorporation of another metal elements into this soluble NP assembly to improve the catalytic activity. Although it was known that the Au/Rh systems were bulk-immiscible, [31][32][33][34] the segregated bimetallic Au/Rh particles still showed improved catalytic activity compared to pure Au or Rh NPs in some reactions. [35][36][37] Encouraged by that, we expected that incorporation of Rh elements in the assembly could enhance the catalytic activity in AB decomposition.…”
Section: Donut Assembly Of Nanoparticles With High Catalytic Efficienmentioning
confidence: 99%
“…19 Consistently, gold rhodium nanoparticles were seen to display either Rh@Au core-shell geometry or ball-cup distribution with Rh partially encapsulated by Au. 20,21 A core@shell distribution is also adopted in Fe@Au NPs. 2224 However, the synthesis way of the NPs, as the overall composition and environment can also lead to the formation of RhAu 25 and FeAu 26 alloys or Rh@Fe core-shell NPs.…”
Section: Introductionmentioning
confidence: 99%